THE ROLE OF THE RESVERATROL AS ANTIOXIDANT IN IMPROVING THE CHEMICAL AND QUALITATIVE PROPERTIES OF CHILLED GROUND BEEF - Enas Y. R. Alawady; Alrubeii, A. M. S. (The Iraqi Journal of Agricultural science)
This study was conducted to evaluate the effects of resveratrol as a natural antioxidant in improving the chemical properties and some qualitative and microbial properties of chilled ground beef stored at 2 C° for 1, 3, 6, 9, and 12 days. The study included 7 different treatments: T1 (control treatment without addition) T2 (Resveratrol 0.10% g/kg) T3 (Resveratrol 0.20% g/kg) T4 (Resveratrol 0.30% g/kg) T5 (Resveratrol %0.40g/kg) T6 (Resveratrol %0.50g/kg) and T7 (Addition of Butylated hydroxyanisole 0.01% BHA). All addition treatments showed a significant (P<0.05) decreases in dry matter percentage of Fat and Ash and increase in protein, moisture and water holding capacity (WHC) percentage as compared with the control treatment at any refrigerated storage time. Thiobarbituric acid (TBA) were lower (P<0.05) in treatments (Resveratrol) as compared with the control treatment at any refrigerated storage time. Resveratrol treated samples recorded lower (P<0.05) total plate count of bacteria during refrigerated storage times . It can be concluded that the resveratrol had positive significant influence on quality characteristics and microbial safety of ground beef meat when stored under refrigeration at 2 C° up to 12 days.